2010
DOI: 10.1016/j.jsb.2010.02.013
|View full text |Cite
|
Sign up to set email alerts
|

12 Arylstibonic acids that inhibit the DNA binding of five B-ZIP dimers

Abstract: Previously, we identified an arylstibonic acid, NSC13778 that specifically binds to the basic region of the C/EBPalpha B-ZIP domain and disrupts DNA binding. We now examine a panel of 14 additional arylstibonic acid derivatives of NSC13778 for their ability to inhibit the DNA binding of five B-ZIP dimers (c-Fos|JunD, VBP, C/EBPalpha, C/EBPbeta, and CREB). They show various specificities at inhibiting the DNA binding of five B-ZIP domains. NSC13746 inhibits the DNA binding of C/EBPbeta and CREB at 100nM and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 43 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…Other studies demonstrated that direct interaction of cyclopentenone 15-deoxy- Δ 12,14 -prostaglandin J 2 (15d-PGJ 2 ) with 269 cysteine of AP-1 protein, and thus contribute to the complex effects of 15d-PGJ 2 on the cellular response to pro-inflammatory agents [ 56 ]. Arylstibonic acid NSC13746 binds specifically to c-Fos/JunD dimer of B-ZIP proteins at micromolar concentrations and can inhibit their DNA-binding activity both in vitro and in vivo [ 57 ]. Expression in the mouse epidermis of A-Fos, a dominant negative form that inhibits AP-1 DNA binding, converts papillomas into benign sebaceous adenomas that are not able to convert into carcinomas [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies demonstrated that direct interaction of cyclopentenone 15-deoxy- Δ 12,14 -prostaglandin J 2 (15d-PGJ 2 ) with 269 cysteine of AP-1 protein, and thus contribute to the complex effects of 15d-PGJ 2 on the cellular response to pro-inflammatory agents [ 56 ]. Arylstibonic acid NSC13746 binds specifically to c-Fos/JunD dimer of B-ZIP proteins at micromolar concentrations and can inhibit their DNA-binding activity both in vitro and in vivo [ 57 ]. Expression in the mouse epidermis of A-Fos, a dominant negative form that inhibits AP-1 DNA binding, converts papillomas into benign sebaceous adenomas that are not able to convert into carcinomas [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further screening of stibonic acids identified additional very active but promiscuous inhibitors of bZip (CREB) and bHLHZip (USF and Mitf) proteins. 297,298 Rudenko and co-workers 299 screened 54 498 molecules for inhibitors of ΔFosB DNA binding. They identified two, C2 and C6, that were active in follow-up assays.…”
Section: Intrinsically Disordered Proteins In Protein–protein Intementioning
confidence: 99%
“…All other proteins used in this study have been described previously, including C/EBP␣ (Krylov et al, 1995), C/EBP␤ (Rishi et al, 2005), CREB (Ahn et al, 1998), CREB-LZ (Ahn et al, 1998), VBP (Moll et al, 2000), VBP-LZ (Moll et al, 2000), Mitf (Rishi et al, 2004), and USF (Rishi et al, 2004). The recombinant proteins were overexpressed in the Escherichia coli BL21 (LysE) strain and purified as described previously (Krylov et al, 1995;Olive et al, 1997;Rishi et al, 2010).…”
Section: Methodsmentioning
confidence: 99%